Current issues of the research process as a component of the protection of the reproductive potential of adolescent girls - V.O. Dynnik; M.L. Vodolazhskyi; T.P. Sydorenko; T.V. Fomina; T.V. Koshman (Zaslavsky O.Yu., 2022)
Background. The medical community extremely needs to conduct scientific research on topical issues of physiology, pathology of the formation of the reproductive system of the body and the organization of medical and preventive measures to preserve the reproductive potential of young people. The study was aimed to improve scientific and informational support for specialists in the field of child and adolescent health protection in pediatric gynecology. Materials and methods. There were studied the publications of research and dissertation works conducted in Ukraine in 2010-2020 in the field of "Pediatric Gynecology"; scientific journals devoted to topical issues of reproductive health of the female population; statistical materials of the Ministry of Health of Ukraine on the analysis of demographic processes.  Information analytics methods were used to analyze them. Results. In Ukraine, research work on topical issues of pediatric gynecology is consistently carried out. During the study period (2010-2020), 23 research projects and 26 dissertations were conducted. According to their implementation, 195 articles, 196 abstracts were published in collections of scientific and practical conferences; 6 book publications, 12 methodological recommendations, 11 informational letters, 39 patents for inventions and utility models, 16 certificates of copyright registration were published. The thematic focus of research is presented as follows: pathophysiological mechanisms of formation of menstrual disorders in adolescent girls; disorders of menstrual function in the age aspect; the influence of socio-economic conditions on the formation of the reproductive system of girls and adolescents; new medical technologies in the field of reproductive health. Conclusions. Further research on the mechanisms of the development of gynecological diseases in adolescent patients in modern society will improve the system of preventive and rehabilitation measures to preserve reproductive potential and improve the quality of life of patients with disorders of the reproductive system.